Soft tissue management at implants: Summary and consensus statements of group 2. The 6th EAO Consensus Conference 2021. (12th October 2021) - Thoma, Daniel S.; Cosyn, Jan; Fickl, Stefan; Jensen, Simon S.; Jung, Ronald E.; Raghoebar, Gerry M.; Rocchietta, Isabella; Roccuzzo, Mario; Sanz, Mariano; Sanz‐Sánchez, Ignacio; Scarlat, Pavel; Schou, Soren; et al.
Abstract: Objectives: The task of working Group 2 at the 6th Consensus Meeting of the European Association for Osseointegration was to comprehensively assess the effects of soft tissue augmentation procedures at dental implant sites on clinical, radiographic and patient‐reported outcome measures (PROMs) including an overview on available outcome measures and methods of assessment. Materials and methods: Three systematic reviews and one critical review were performed in advance on (i) the effects of soft tissue augmentation procedures on clinical, radiographic and aesthetic outcomes, (ii) reliability and validity of outcome measures and methods of assessment and (iii) PROMs applied in clinical studies for soft tissue augmentation procedures at dental implant sites. Major findings, consensus statements, clinical recommendations and implications for future research were discussed in the group and approved during the plenary sessions. Results: The four reviews predominantly revealed: Soft tissue augmentation procedures in conjunction with immediate and delayed implant placement result in superior aesthetic outcomes compared to no soft tissue augmentation in the zone of aesthetic priority. Soft tissue augmentation procedures have a limited effect on marginal bone level changes compared to implant sites without soft tissue augmentation. Clinically relevant parameters (gingival index, mucosal recession) and plaque control improve at implant sites when the width of keratinised mucosa is increased. A variety of aesthetic indices have been described with good reliability. Pink Esthetic Score and Complex Esthetic Index are the most validated aesthetic indices for single implants, though. Superimposed digital surface scans are most accurate to assess profilometric tissue changes. PROMs following soft tissue augmentation procedures have been assessed using various forms of questionnaires. Soft tissue augmentation had a limited effect on PROMs. Conclusions: Soft tissue augmentation procedures are widely applied in conjunction with implant therapy. Depending on the indication of these interventions, clinical, radiographic and aesthetic outcomes may improve, whereas the effect on PROMs is limited.